Validation of a test battery to assess aquatic literacy of children aged 6 to 12 across europe - Potdevin, F.; De Martelaer, K.; D'Hondt, E.; van Droogenbroeck, L.; Consortium, A.; Mekkaoui, L. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Assessing the level of protective aquatic skills is one challenge of the ALFAC (Aquatic Literacy For All Children) project. Stallman et al.'s (2017)1 model describes the fundamental aquatic skills (FAS) to be mastered in isolation to protect children from drowning. However, the use of combined tests is extremely relevant in assessing their ability to cope with different scenarios that can lead to drowning accidents. The presentation objective is to expose the aquatic ALFAC "parcours" to assess the capacity of children to combine aquatic tasks while making decisions in-action.